The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2757608
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of the oxide-semiconductor interface in annealed Al2O3∕4H-SiC structures

Abstract: Al 2 O 3 films with different thicknesses have been deposited on n-type ͑nitrogen-doped͒ 4H-SiC͑0001͒ epitaxial samples by atomic layer chemical vapor deposition at 300°C and subsequently annealed in Ar atmosphere at temperatures up to 1000°C. The Al 2 O 3 /4H-SiC structures were analyzed by x-ray photoelectron spectroscopy ͑XPS͒, secondary ion mass spectrometry ͑SIMS͒, and transmission electron microscopy ͑TEM͒. The XPS and SIMS results indicate that the average composition in the wider interface area does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The interlayer thickness increased after annealing at 1000°C in Ar, which also triggered Si diffusion into the dielectric layer as evidenced by secondary ion mass spectrometry. 5 The thickness of a SiO 2 interlayer has significant impact on channel mobility for Al 2 O 3 / 4H-SiC MOSFETs. 6 Thus, controlling the transport of oxygen through Al 2 O 3 is mandatory.…”
Section: Enhancement In Interface Robustness Regarding Thermal Oxidatmentioning
confidence: 99%
“…The interlayer thickness increased after annealing at 1000°C in Ar, which also triggered Si diffusion into the dielectric layer as evidenced by secondary ion mass spectrometry. 5 The thickness of a SiO 2 interlayer has significant impact on channel mobility for Al 2 O 3 / 4H-SiC MOSFETs. 6 Thus, controlling the transport of oxygen through Al 2 O 3 is mandatory.…”
Section: Enhancement In Interface Robustness Regarding Thermal Oxidatmentioning
confidence: 99%
“…Amorphous alumina (AlO x ) has been considered in several technological applications, not only because of passivating and insulating properties, but also because of its high dielectric constant and reflectivity in the visible. The AlO x thin layer can be deposited via a variety of techniques ranging from vacuum to nonvacuum techniques such as sputtering, chemical vapor deposition or atomic layer deposition . However, it is well-known that these processes introduce impurities from precursor chemical species used during film deposition, as hydrogen. Unfortunately, it is difficult to quantitatively probe the H content in a film, particularly unbonded H formed during annealing under H 2 atmosphere and incorporated within AlO x bulk or at the interface AlO x /Si creating blistering phenomena .…”
mentioning
confidence: 99%
“…Avice et al prepared films of aluminium oxide on n-type (nitrogen doped) 4H-SiC (001) epitaxial samples using atomic layer chemical vapour deposition. 298 The samples were deposited at 300 C and were then annealed in an argon atmosphere at 1000 C. The structures of the materials were analyzed by a series of techniques including SIMS, XPS and TEM. The SIMS and XPS results indicated that the average composition in the wider interface was not changed significantly by the annealing process.…”
Section: Semiconductors Wang and Colleagues Reported A Newmentioning
confidence: 99%